Answer:
Given the expression:
1.
![-4^2](https://tex.z-dn.net/?f=-4%5E2)
we know:
![4^2 = 4 \times 4 = 16](https://tex.z-dn.net/?f=4%5E2%20%3D%204%20%5Ctimes%204%20%3D%2016)
then;
![-4^2 = -16](https://tex.z-dn.net/?f=-4%5E2%20%3D%20-16)
Therefore, the value of expression
is -16 i.e negative.
2.
![(-4)^2](https://tex.z-dn.net/?f=%28-4%29%5E2)
we know:
![4^2 = 4 \times 4 = 16](https://tex.z-dn.net/?f=4%5E2%20%3D%204%20%5Ctimes%204%20%3D%2016)
![(-1)^2 = 1](https://tex.z-dn.net/?f=%28-1%29%5E2%20%3D%201)
then;
![(-4)^2 = (-1)^2 \cdot (4)^2= 16](https://tex.z-dn.net/?f=%28-4%29%5E2%20%3D%20%28-1%29%5E2%20%5Ccdot%20%284%29%5E2%3D%2016)
Therefore, the expression
is 16 i.e Positive.
3.
![4^2](https://tex.z-dn.net/?f=4%5E2)
we know:
![4^2 = 4 \times 4 = 16](https://tex.z-dn.net/?f=4%5E2%20%3D%204%20%5Ctimes%204%20%3D%2016)
then;
![4^2 = 16](https://tex.z-dn.net/?f=4%5E2%20%3D%2016)
Therefore, the expression
is 16 i.e Positive.
Answer:
![2x {}^{2} - 8 = 0](https://tex.z-dn.net/?f=2x%20%7B%7D%5E%7B2%7D%20%20-%208%20%3D%200%20)
Step-by-step explanation:
![(x-2) (2x+4) = 0\\ 2x {}^{2} + 4x - 4x - 8 = 0 \\ 2x {}^{2} - 8 = 0](https://tex.z-dn.net/?f=%28x-2%29%20%282x%2B4%29%20%20%3D%200%5C%5C%202x%20%7B%7D%5E%7B2%7D%20%20%20%2B%20%204x%20-%204x%20-%208%20%3D%200%20%5C%5C%202x%20%7B%7D%5E%7B2%7D%20%20-%208%20%3D%200)
Answer: 99% sure its (1,4)
Step-by-step explanation: